2000
DOI: 10.1073/pnas.220394197
|View full text |Cite
|
Sign up to set email alerts
|

A dibasic motif involved in parathyroid hormone-induced down-regulation of the type IIa NaPi cotransporter

Abstract: Type II NaPi cotransporters are expressed in the apical membrane of Pi-(re)absorbing epithelia: the type IIa in renal proximal tubule and the type IIb in small intestine. Parathyroid hormone (PTH) leads to a retrieval from the apical membrane of the type IIa NaPi cotransporter. The type IIa cotransporter is also expressed in opossum kidney (OK) cells, and its expression is under the control of PTH. In the present study, we identified the molecular ''domains'' involved in the PTH-induced retrieval of the type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 54 publications
(69 reference statements)
1
34
0
Order By: Relevance
“…Although putative endocytic motifs such as tyrosine-or di-leucine-based motifs are contained within the amino acid sequence of NaPi-lla, mutations of these motifs did not affect the retrieval of NaPi-lla [50]. Instead, a dibasic amino acid motif (KR), most likely localized within an intracellular loop, was found to be required for internalization and degradation of NaPi-lla [56]. The absence of this KR motif in the NaPi-llc protein could explain the different endocytic rates of the NaPi-lla and NaPi-llc cotransporters after PTH stimulation.…”
Section: Parathyroid Hormonementioning
confidence: 99%
“…Although putative endocytic motifs such as tyrosine-or di-leucine-based motifs are contained within the amino acid sequence of NaPi-lla, mutations of these motifs did not affect the retrieval of NaPi-lla [50]. Instead, a dibasic amino acid motif (KR), most likely localized within an intracellular loop, was found to be required for internalization and degradation of NaPi-lla [56]. The absence of this KR motif in the NaPi-llc protein could explain the different endocytic rates of the NaPi-lla and NaPi-llc cotransporters after PTH stimulation.…”
Section: Parathyroid Hormonementioning
confidence: 99%
“…The two charged amino acids in the type IIa cotransporter (K 503 R 504 ) are replaced by uncharged residues in type IIb (N 520 I 521 ), which is not regulated by PTH. The results of chimera experiments with type IIb indicate that this motif is important for PTH-induced endocytosis [29].…”
Section: Trafficking Of Type Iia Na/pi Cotransportermentioning
confidence: 99%
“…By the yeast two-hybrid approach, several proteins were identified that interact with type IIa transporter protein and are localized either in the brush border or in the subapical compartment of proximal tubular cells [25][26][27][28]. Karim-Jimenez et al [29] indicated that the N-and C-terminals are not required for the PTHinduced internalization, whereas the region between residues 216 and 658 seems to be necessary. This region contains two putative intracellular loops with sequences in the last intracellular loop that are highly conserved between the types IIa and IIb proteins.…”
Section: Trafficking Of Type Iia Na/pi Cotransportermentioning
confidence: 99%
“…This model incorporates predictions from biochemical and biophysical studies including epitope labeling, cysteine scanning mutagenesis and in vitro glycosylation assays (for review see: ( ). The C-terminal region is important for targeting, hormonal regulation and proteinprotein interactions, for example the TRL motif in the C-terminal plays a role as a PDZ binding motif Karim-Jimenez et al, 2001), and a KR motif located in an intracellular linker region (Fig 2A) is critical for PTH sensitivity (Karim-Jimenez et al, 2000). Sequence analysis reveals an inverted repeat motif that is conserved amongst SLC34 isoforms and homologs in all phyla (Werner and Kinne, 2001).…”
Section: Structure-function Relationships Of Slc34 Proteinsmentioning
confidence: 99%